Blood Pressure Control: A Need of Primary Care - Singh, Jai P; Singh, Prabhu N; Srivastava, Anurag; Pitale, Smita; Mohammed, Syeed E (National Journal of Community Medicine, 2013)
Background: The most common cause of mortality in geriatric patients is cardiovascular disease (CVD). Hypertension (HTN), a risk factor for CVD and the number one reason for primary care visits in the India, affects 20-50% of geriatric population. Methodology: A community based cross sectional study was carried out in the field practice area of Urban health training center (UHTC), dept. Of community medicine, NKP Salve Institute of Medical Sciences and Research Center, Nagpur. A total of 400 subjects aged ≥ 60 years were screened for hypertension. Diagnosis of hypertension was based on the JNC-VII. Results: Author observed that prevalence of hypertension was 34.75%. Family history of Hypertension, BMI ≥ 25 & Stress as risk factors were highly significant with hypertension (p<0.001,) while Diabetes, Lack of exercise & Alcohol factors were significant with hypertension (p<0.05) Conclusion: Routine screening of geriatric subjects and counseling of diagnosed cases were suggested for behavioral change.